FRI0240 The clinical course of the acute deep vein thrombosis of the legs in behÇet's syndrome. (23rd January 2014) - Ozguler, Y.; Melikoglu, M.; Cetinkaya, F.; Ugurlu, S.; Tascilar, K.; Yazici, H.
Abstract : Background: 15-50% of patients with Behçet's syndrome have vascular involvement (BS). Lower extremity deep vein thrombosis (LEDVT) makes up 70% of all vascular involvement (1, 2). Objectives: The aim of this study was to determine the clinical course of LEDVT about which there has been little data. Methods: Consecutive BS patients attending our BS outpatient clinic were included after an acute or subacute first episode of LEDVT in one leg. They might have had previous contralateral LEDVT. The same radiologist performed a structured and detailed lower extremity Doppler ultrasonography (US). All deep veins, VCI and major superficial veins were examined at 1, 3, 6, 18 and 24 months after the index event. Nodular lesions that evolved during follow-up were also examined for their US structure to differentiate between superficial vein thrombosis and erythema nodosum. Results: Within 20 months 31 patients (4F, 27M) with LEDVT in a previously uninvolved leg were studied. 10 patients had had a previous episode of LEDVT in the opposite leg. Mean age was 29.5±7, mean disease duration since disease onset was 49.5±34.6, and the mean follow-up duration during the study was 13.4±6.2 months. Veins involved in order of frequency were popliteal vein (42%), superficial femoral vein (31%), crural veins (29%) and common femoral vein (27%). VCI was involved in 3 (5%) patients. 14 patients (45%) relapsed during follow-up. 11 patients relapsed with a superficial thrombophlebitis and 5 patients relapsed with a new deep vein thrombosis. Mean time to relapse was 2.83±1.99 months when the relapse was a superficial thrombophlebitis and 6.0±2.3 months when the relapse was a LEDVT (P=0.001). Only 3 out of 19 patients who had a recanalization (≥50%) at month 3 follow-up had a relapse whereas a relapse was observed in 11 of the 12 patients with poor recanalization (<50%) (P=0.001). All 3 patients with VCI involvement had venous skin ulcers in the lower extremity and these 3 patients were also the only patients with skin ulcers in the whole group. 17/31 (55%) patients developed nodular lesions during the study. 13/17 had had previous episodes of nodular lesions while in 4 patients these appeared for the first time. Doppler ultrasonographic examination of these nodules revealed superficial thrombophlebitis in 12 (70%). Conclusions: The more common vascular relapse after an episode of LEDVT is superficial thrombophlebitis. Relapses of a superficial thrombophlebitis occur earlier than relapses with a LEDVT. Poor recanalization of the index LEDVT at 3 months is associated with relapses. The presence of skin ulcers seems to go along with inferior vena caval thrombosis. As expected, LEDVT in BS is associated more with superficial thrombophlebitis than with erythema nodosum-type lesions (3). References: Melikoglu M, Ugurlu S, Tascilar K, et al. Large vessel involvement in Behçet's syndrome: a retrospective survey. Ann Rheum Dis. 2008; 67 (Suppl II): 67. Sarica-Kucukoglu R, Akdag-Kose A, Kayabali M, et al; Vascular involvement in Behçet's disease: a retrospective analysis of 2319 cases. Int J Dermatol. 2006; 45: 919 – 921 Tunc R, Keyman E, Melikoglu M, Fresko I, Yazici H. Target organ associations in Turkish patients with Behçet's disease: a cross sectional study by exploratory factor analysis. J Rheumatol. 2002; 29:2393-6 Disclosure of Interest: None Declared